Petrology and geochemistry of Northwest Africa 5480 diogenite and evidence for a basin-forming event on Vesta - Yamaguchi, A.; Barrat, Jean-Alix; Shirai, N.; Ebihara, M. (Meteoritics & Planetary Science, 2015)
International audience We performed a petrological and geochemical study of an olivine diogenite, Northwest Africa (NWA) 5480. NWA 5480 is a crystalline stone, but shows a heterogeneous texture. Olivine aggregates and grains of olivine and chromite display resorption textures set in a crystalline pyroxene matrix. Large olivine aggregates are penetrated by pyroxene matrix. Flow textures are observed near olivine aggregates. Olivine, chromite, and pyroxene show minor chemical zoning, implying relatively rapid cooling. NWA 5480 contains a significant amount of platinum group elements with chondritic relative proportions. All this evidence supports that NWA 5480 is an impact-melt breccia from a target composed of olivine and pyroxene-rich lithologies. Such impact melt would have formed by melting crustal materials, possibly during one of the impacts that formed the South Pole basins on Vesta.